Results of the 2000 census of wild reindeer on the Taimyr Peninsula - Kolpashchikov, Leonid A.; Yakushkin, Gregory D.; Kokorev, Yakov I. (Rangifer, 2003)
We conducted a census of wild reindeer (Rangifer tarandus) on the Taimyr Peninsula during 21-25 July 2000. This was the eighteenth aerial population census of wild reindeer on the Taimyr since counts began in 1959. Prior to the census, we conducted reconnaissance flights to identify areas of reindeer concentration. After the reindeer became aggregated, we estimated group size both visually and by photographing the larger groups. Unusually hot and dry weather (temperatures of 25-30 °C) and a high density of mosquitoes during the census likely forced the reindeer to group into unusually large concentrations. In late July most of the reindeer in the Taimyr population were distributed in two groupings that contained at least 450 000 animals, and one area that contained about 110 000. Smaller groups found during the census and the estimated 43 000 resident wild reindeer that were not counted during the census brought the total minimum population estimate to about 1 040 000. The maximum number of wild reindeer present could have been as high as about 1 100 000.